Synthesis and application of Aromatic Schiff base waterborne polyurethane as visible-light triggered self-healing polymer and anticorrosion coating using h-BN/GO/NiO nano-composite - Masoumeh Kianfar; Mir Saeed Seyed Dorraji; Mohammad Hossein Rasoulifard; Alireza Rahimi; Sohrab Rahmani (Polymer Testing)
Herein, a self-healing waterborne polyurethane (WPU) based on a novel visible light-stimulated healing agent from the aromatic Schiff base family (SBWPU) was synthesized. Moreover, this polymer exhibited remarkable mechanical properties, making it an ideal matrix for the preparation of a new nano-composite coating using hexagonal-boron nitride/graphene oxide/nickel oxide (h-BN/GO/NiO) nano-composite for anti-corrosion applications. SBWPU containing 15 wt % of synthesized healing agent (SBWPU-15) demonstrated favorable healing properties (80.03 %) under a visible light lamp after 24 h (at ambient temperature). SBWPU containing 20 % of the healing agent (SBWPU-20) showed high mechanical properties (20.80 MPa) and an increase in its hydrophobic properties. Additionally, its water absorption rate decreased, making it an attractive option as a polymer matrix for anti-corrosion coating applications. The nano-composite coatings (CSBWPU) were formulated by introducing varying amounts of h-BN/GO/NiO into the SBWPU-20. The coatings displayed an increase in contact angle and a decrease in water absorption rate. The electrochemical impedance spectroscopy (EIS) results revealed that the 0.75-CSBWPU, containing 0.75 % nano-composite, had the highest corrosion resistance (1.58 × 1010 Ω cm2) after 90 days of immersion in seawater. This work offers a potentially helpful concept for developing an eco-friendly, secure, uncomplicated accessibility self-healing polymeric system with controllable mechanical features, which are also favorable for designing novel corrosion protection composite coatings.